Arabic Literary Influences and Representations in the Poetry of Iqbal: A Cultural and Thematic Analysis - Ahamed Zubair K M A Dr; Nahvi Muhiyadeen Lebbai; M.Yasar Arafath Ali; N Sheik Hameed M; Luthfur Rahman (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This research examines the representations and influence of Arabic literature in the poetry of Muhammad Iqbal, renowned as the poet of the East. Despite never traveling to Arab lands, Iqbal's profound mastery of the Arabic language and literature profoundly shaped his poetic style, themes, and symbolism. The study employs a literary-analytical approach to identify how Iqbal drew from classical Arabic poetry, Quranic texts, and Arab cultural history. Through close reading of poems such as